Conflict and Production: An Application to Natural Resources - Katharina Wick (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2007)
We present a Stackelberg model of conflict, in which contestants have limited endowments to be put in two separate sectors, thus incorporating salient features of many conflicts. The model is applied to the case of conflict over natural resources. Consistent with amounting empirical evidence regarding a so-called "resource curse", we find that the relation between conflict intensity and resource rents is non-monotonous, and that the economy's income growth rate may be negatively affected by resource abundance.
Keywords: O13; Q32; D74; 330; Resource curse; exhaustible resources; civil war; economic performance and resources